P258 Real-world secukinumab retention, response rates and adverse events in the treatment of PsA and axSpA. (20th April 2020) - Tindell, Alistair; Batool, Saira; McGucken, Andrew; Siebert, Stefan
Abstract: Background: Secukinumab, an IL-17A inhibitor, has been licensed for use in the United Kingdom for both axial spondyloarthritis (axSpA) and psoriatic arthritis (PsA) for several years. Despite this there is minimal published data on its use out with randomised controlled trials. We present here the collated real-world rheumatology experience of secukinumab use in Glasgow. Methods: Patients who have ever received secukinumab for any rheumatology indication were identified using available medical records (from 14/05/2012 to 18/09/2019). Diagnosis, baseline demographics, disease activity at baseline and at 6 months, and whether patients are still currently on secukinumab was recorded. Primary inefficacy was defined as stopping treatment due to inefficacy ≤6 months. Reasons for discontinuation were also recorded. As disease activity scores were variably recorded, the primary outcome was retention rate as a surrogate for efficacy and lack of adverse event. Patients only included in disease scores if scores available both at baseline and 6 months. Results: 352 patients (with 530 patient-years of exposure) identified. 251 (71.3%) patients currently remain on secukinumab. 301 of 336 (89.6%) patients remained on drug at six-month review (16 await review). Characteristics and response of two main diagnostic groups listed in Table 1 (Note: 3 patients had SAPHO, 5 had Juvenile Idiopathic Arthritis, 1 had reactive arthritis). Common adverse events were infections (11 patients), rash and/or pruritis (6 patients), mood change and/or fatigue (4 patients). Three patients developed inflammatory bowel disease (IBD) subsequent to starting secukinumab. Five patients had pre-existing IBD, none of which flared on secukinumab. Two patients required hospitalisation for abscesses whilst on secukinumab. One patient had a stroke and one patient had a myocardial infarction whilst on secukinumab - both patients had multiple risk factors for cardiovascular disease. No malignancies identified. Three patients died, with none felt related to secukinumab (cerebellar haemorrhage in warfarinised patient with high INR; pneumonia six months after switching from secukinumab to tocilizumab; one out of hospital death over one year after stopping secukinumab). Conclusion: In this real world cohort of patients with axSpA and PsA, secukinumab retention rates at 6 months are high with no new safety signals identified. Disclosures: A. Tindell None. S. Batool None. A. McGucken None. S. Siebert Consultancies; S.S. has received speaker or consultation fees or honoraria from AbbVie, UCB, Janssen, Boehringer Ingelheim, Novartis, Celgene. Honoraria: S.S. has received speaker or consultation fees or honoraria from AbbVie, UCB, Janssen, Boehringer Ingelheim, Novartis, Celgene. Grants/research support; S.S has received funding for research/ grants from Pfizer, Janssen, BMS, Celgene, UCB, Boehringer Ingelheim, Novartis, GSK.